Comparative characteristics of green microalgae parachlorella kessleri and chlorella vulgaris as a protein additive - N. K. Kalantaryan; L. A. Stepanyan; A. S. Dadayan; E. V. Minasyan; V. B. Goginyan (ՀՀ ԳԱԱ հրատ.)
The comparative evaluation of green unicellular microalgae Parachlorella kessleri and Chlorella vulgaris biomass as an additional protein and essential amino acids source has been performed. Проведена сравнительная оценка зеленых одноклеточных микроводорослей Parachlorella kessleri и Chlorella vulgaris в качестве дополнительных источников белка и аминокислот, в том числе незаменимых. Իրականացվել է Parachlorella kessleri և Chlorella vulgaris կանաչ միկրոջրիմուռների կենսազանգվածների համեմատական գնահատում՝ որպես լրացուցիչ սպիտակուցների և անփոխարինելի ամինաթթուների աղբյուր:
Keywords: Analytic Chemistry